0968 Sleep-disordered Breathing In Schaaf-yang Syndrome. (27th May 2020) - Powell, W; Rech, M; Schaaf, C; Wrede, J
Abstract: Introduction: Schaaf-Yang Syndrome (SYS) is a genetic disorder caused by truncating variants in the MAGEL2 gene located in the maternally imprinted, paternally expressed Prader-Willi syndrome (PWS) region at 15q11-13. The SYS phenotype shares features with PWS, a disorder with known high incidence of central and obstructive sleep apnea (OSA). However the spectrum of sleep-disordered breathing in SYS has not been described. Methods: We performed a retrospective analysis of polysomnograms from 22 of the known 115 patients with molecular diagnosis of SYS. Sleep characteristics including total sleep time, latency, efficiency, % sleep stages, apnea-hypopnea index (AHI), obstructive index, central index, and oxygenation were analyzed for the whole group and by truncation location (c.1996dupC variants [n=11] or other locations [n=11]). Only the initial diagnostic study or initial diagnostic portion of a split-night study was used in analysis (analytic n=21). Results: We collected 33 sleep study reports from 22 patients, ages 2 months - 18.5 years. Mean analyzed sleep time was 357 minutes (129-589 min) with mean sleep efficiency of 71.45% (45-94%) and sleep latency of 24.8 minutes (0-146 min). The mean apnea-hypopnea index (AHI) was 19.1/hr (0.9 -49/hr) with mean obstructive AHI of 16.3 (0.6-49/hr). Mean central index was 2.8/hr (0-14/hr). 18/21 (86%) were diagnosed with OSA, and 13/21 (62%) with moderate or severe OSA (oAHI >5/hr). Central sleep apnea was diagnosed in 2/21 (9.5%). 15 studies reported periodic limb movement index (PLMI) with mean of 7.8 (0-67/hr) and 4/15 (26%) with PLMI >5. Comparison of genotype groups did not reveal any difference in presence of OSA or severity of OSA. Conclusion: OSA is frequently identified on polysomnography in patients with SYS. Central sleep apnea is less common, which is in contrast to PWS. The majority of patients with OSA had moderate or severe OSA, and 47% had severe OSA. Support: N/A